GAMBARAN PARAMETER KIMIA DAN FISIKA PADA AIR LIMBAH PABRIK TAHU DI KELURAHAN MANGGONG NGADIREJO TEMANGGUNG TAHUN 2023 - Dwi Atin Faidah Atin Faidah; Bintari Nunik Kristina (Jurnal Ilmiah Medsains, 2023)
Waste is the residue of activity. One of the food processing industries that produces a lot of waste is the tofu industry. The dominant waste is wasted in liquid form and has the potential to pollute the waters. The tofu industry in Kelurahan Manggong does not yet have a wastewater treatment plant, so tofu waste is directly discharged into water bodies and research on tofu liquid waste has never been carried out. The aim of this research is to describe the chemical and physical parameters of tofu factory wastewater in Manggong Ngadirejo Village, Temanggung in 2023. This research is an observational study with a cross sectional approach. The research was carried out in May 2023. The population for this study was all liquid waste produced from seven factories in Manggong Village which was channeled through communal wastewater channels to be discharged into water bodies. The sample in this study was tofu liquid waste which was at the outlet of the wastewater channels from seven factories which flowed through communal wastewater channels to enter water bodies. Samples were taken as much as approximately 5 liters using a jerry can. Sampling was carried out 3 times on different days in a row when tofu production took place. Then the samples were taken and examined at the Banjarnegara Regency Regional Health Laboratory. Based on the research results, it can be seen that the inspection results based on the Minister of Environment Regulation Number 5 of 2014, the contents of BOD, TSS, pH and temperature are in accordance with the established quality standard requirements. While the COD content in samples one and three did not comply with the specified quality standards. Making a wastewater treatment plant (WWTP)can be done so that the waste that is disposed of can be treated beforehand and is safe if discharged into water bodies or rivers. Examination of the chemical and physical parameters of tofu waste is carried out routinely to evaluate the effectiveness of the WWTP.